Incidence and causes of repeat breeding in crossbred dairy cows - a retrospective study - SELVARAJ, P; KUMAR, HARENDRA; BHIST, G S (The Indian Journal of Animal Reproduction, 2023)
The data for the present study were collected from Military Dairy Farm, Bareilly for a period of 10 years and the effectof season, parity, breed, milk yield and periparturient diseases on incidence of repeat breeding (RB) were analysed. The overallincidence of RB in Friesian x Sahiwal crossbred cows was 28.38 percent. The incidence was higher in spring calved than other seasons.The incidence of RB was also found higher (35.68%) during second than other parities. An increased incidence of RB was recordedin higher crosses (7/16, 5/8 and 3/4) and high yielders (36.10%). Abnormal calvings had significant influence on incidence of RB.
Keywords: Repeat breeding; crossbred cows